2019
DOI: 10.1002/cbin.11225
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor E2F4 is a positive regulator of milk biosynthesis and proliferation of bovine mammary epithelial cells

Abstract: The transcription factor E2F4 is a key determinant of cell differentiation and cell‐cycle progression, but its function and regulatory mechanism are not completely understood. Here, we report that E2F4 acts as a positive regulator of the biosynthesis of milk components and proliferation of bovine mammary epithelial cells (BMECs). Overexpression of E2F4 in BMECs resulted in the upregulation of β‐casein, triglyceride, and lactose levels and increased cell proliferation, whereas E2F4 knockdown by small interferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Consistent with this study, the peptide hormone (kisspeptin-10) and optimal EAAs had resulted in higher cell viability with an increase in S and G2/M phases compared to that of control cells in BMECs [14,43]. In addition, previous studies have reported that the increase in the S and G2/M phases during the progression of the cell cycle promotes cell proliferation along with an increase in PCNA and cyclin B1 levels in BMECs and mouse mesenchymal stem cells [44][45][46]. Moreover, our data showed that H-and HAtreated cells had higher DAPI-stained areas, thereby indicating an increase in cell proliferation and cell numbers compared to that in control cells (Figure 6).…”
Section: Wwwanimbiosciorg 1763supporting
confidence: 86%
“…Consistent with this study, the peptide hormone (kisspeptin-10) and optimal EAAs had resulted in higher cell viability with an increase in S and G2/M phases compared to that of control cells in BMECs [14,43]. In addition, previous studies have reported that the increase in the S and G2/M phases during the progression of the cell cycle promotes cell proliferation along with an increase in PCNA and cyclin B1 levels in BMECs and mouse mesenchymal stem cells [44][45][46]. Moreover, our data showed that H-and HAtreated cells had higher DAPI-stained areas, thereby indicating an increase in cell proliferation and cell numbers compared to that in control cells (Figure 6).…”
Section: Wwwanimbiosciorg 1763supporting
confidence: 86%
“…Both E2F4 and E2F6 belong to the ubiquitous E2F family of transcription factors which control cell proliferation and terminal fate (38)(39)(40). E2F4 was initially categorized as the major repressor of cell cycle progressions, however, recent research showed that E2F4 acted in part as a transcriptional activator that promoted the expression of cell cycle genes in mouse embryonic stem cells (41), functioned as a positive regulator of milk biosynthesis and proliferation of bovine mammary epithelial cells (42) and it could positively regulate hepatitis B virus (HBV)transcription by binding the core promoter of HBV covalently closed circular DNA (43). In this study, the positive regulation of E2F4 on G allele supported the point that E2F4 regulated diverse gene expression programs in cell fate decisions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, under growth arrest conditions, E2F4 can repress a common set of genes involved in mitochondrial biogenesis and metabolism [ 66 ]. Moreover, E2F4 participates in the differentiation of multiple cell types, including the differentiation of myocytes [ 22 , 36 , 67 , 68 , 69 ], neural cells [ 30 , 70 ], adipocytes [ 71 , 72 , 73 , 74 ], hematopoietic cells [ 75 ], chondrocytes [ 76 ], extra-embryonic tissues [ 77 ], endothelial cells [ 78 ], epithelial cells [ 79 ], and multiciliated cells [ 80 , 81 ]. E2F4 can also regulate eye and brain patterning [ 82 , 83 , 84 , 85 ], as well as endocytosis and water channel transport in the testes [ 81 ].…”
Section: E2f4 As a Multifactorial Regulatormentioning
confidence: 99%